Documentary in a Changing State : Ireland since the 1990s - O'Connell, Dióg; MacKeogh, Carol (Book collections on Project MUSE., 2012)
This collection of essays examines the role of Irish documentary in film and television as Ireland experienced dramatic shifts in its social and political make-up in recent decades.